2021
DOI: 10.1111/phpp.12654
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological findings of chronic actinic dermatitis

Abstract: Chronic actinic dermatitis (CAD) is a photosensitive disorder, which is probably mediated by immunological factors, presented as pruritic eczematous lesions on sun-exposed area. 1 Generalized erythroderma could also be seen in severe cases. CAD has been reported all over the world, and the incidence of that was thought to be related to sun exposure time (hours) and air quality. 2 Although all races and skin types could be involved, it commonly affects men older than 50-year-old who often going outside. 3 The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 30 publications
(53 reference statements)
0
16
0
Order By: Relevance
“…As well, patients are very sensitive to UV, which manifests as a relapse and aggravation of disease after a short period of UV irradiation. 24 In previous studies, we observed significant skin barrier damage in CAD patients. 25 Skin barrier damage causes external antigens to easily pass through the damaged tight junction structure.…”
Section: Discussionmentioning
confidence: 79%
“…As well, patients are very sensitive to UV, which manifests as a relapse and aggravation of disease after a short period of UV irradiation. 24 In previous studies, we observed significant skin barrier damage in CAD patients. 25 Skin barrier damage causes external antigens to easily pass through the damaged tight junction structure.…”
Section: Discussionmentioning
confidence: 79%
“…UVR plays a crucial role in CAD pathogenesis, inducing both local and systematic negative effects. Furthermore, increased levels of eosinophils and total IgE are common in CAD patients, 4,12 although the precise mechanism underlying this phenomenon remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased levels of eosinophils and total IgE are common in CAD patients, 4,12 although the precise mechanism underlying this phenomenon remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAD is an immune-mediated photodermatosis. As the disease progresses, the lesioned skin becomes rough and thickened, with mossy lesions and increased pruritus, and patients may even scratch the skin and suffer complications such as local skin infections and artificial dermatitis [15,16].…”
Section: Discussionmentioning
confidence: 99%